The Role of Social Media in Realizing Good Governance - Rifan T, Vicko Wahyu; Meilana Rifqi, Achmad Daffa; Al-Fatih, Sholahuddin (LEGAL BRIEF, 2025)
This study aims to analyze the role of social media in influencing transparency and performance of state institutions as an effort to realize the principle of good governance. Using a qualitative approach with legal research methods, this study explores the dynamics of public communication on digital platforms and its implications for the accountability of state institutions. The results of the analysis show that social media accelerates the flow of information, increases public participation, but the increasingly rapid development of social media is a challenge in realizing good governance. However, the challenges in the form of the spread of disinformation and polarization of public opinion are also consequences that must be anticipated. These findings strengthen the argument that social media has strategic potential in strengthening good governance in Indonesia, provided it is supported by adaptive regulations and massive collaboration